Yield of additional genetic testing after chromosomal microarray for diagnosis of neurodevelopmental disability and congenital anomalies: a clinical practice resource of the American College of Medical Genetics and Genomics (ACMG). (October 2018) - Waggoner, Darrel; Wain, Karen; Dubuc, Adrian; Conlin, Laura; Hickey, Scott; Lamb, Allen; Martin, Christa; Morton, Cynthia; Rasmussen, Kristen; Schuette, Jane; Schwartz, Stuart; Miller, David
Abstract Purpose Chromosomal microarray (CMA) is recommended as the first-tier test in evaluation of individuals with neurodevelopmental disability and congenital anomalies. CMA may not detect balanced cytogenomic abnormalities or uniparental disomy (UPD), and deletion/duplications and regions of homozygosity may require additional testing to clarify the mechanism and inform accurate counseling. We conducted an evidence review to synthesize data regarding the benefit of additional testing after CMA to inform a genetic diagnosis. Methods The review was guided by key questions related to the detection of genomic events that may require additional testing. A PubMed search for original research articles, systematic reviews, and meta-analyses was evaluated from articles published between 1 January 1983 and 31 March 2017. Based on the key questions, articles were retrieved and data extracted in parallel with comparison of results and discussion to resolve discrepancies. Variables assessed included study design and outcomes. Results A narrative synthesis was created for each question to describe the occurrence of, and clinical significance of, additional diagnostic findings from subsequent testing performed after CMA. Conclusion These findings may be used to assist the laboratory and clinician when making recommendations about additional testing after CMA, as it impacts clinical care, counseling, and diagnosis.